The Association between Religiosity and Hba1c Level in Patients with Type 2 Diabetes Mellitus: A Systematic Review - Adnan, Muhammad Luthfi; Rahmawati, Riana (IIUM Medical Journal Malaysia, 2024)
Glycemic control poses a challenge in the management of type 2 diabetes mellitus (T2DM). Religiosity can influence a patient’s coping strategies with the disease. However, the relationship between patient religiosity and glycemic control has not been thoroughly explored. In this systematic review, we assessed the relationship between religiosity and glycemic control in patients with T2DM. Using PubMed and Google Scholar, we included articles published in English from 2011 onwards that quantitatively examined religiosity and its relationship with glycemic control based on the glycated hemoglobin (HbA1c) levels. Four studies from four different countries were included, employing varying measurement tools to assess religiosity. The HbA1c level was significantly related to the Diabetes Fatalism Index (p<0.05) and with general gratitude and gratitude to God, as assessed using the Multidimensional Measurement of Religiousness. Religiosity may alleviate stress-related diseases and enhance diabetes care. One study showed a relationship between the HbA1c levels and the Beliefs and Values score amongst Muslims only. Two studies reported a significant correlation between religiosity and HbA1c levels. Reducing fatalistic beliefs and improving gratitude to God could be a viable strategy for helping patients manage T2DM. Further studies are needed to promote such an approach in T2DM management.